Effect of the Innovative Running Shoes With the Special Midsole Structure on the Female Runners’ Lower Limb Biomechanics - Fu, Fengqin; Guo, Lianming; Tang, Xunfei; Wang, Jiayu; Xie, Zhihao; Fekete, Gusztáv; Cai, Yuhui; Hu, Qiuli; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2022)
The study aimed to research the effects of innovative running shoes (a high heel-to-toe drop and special structure of midsole) on the biomechanics of the lower limbs and perceptual sensitivity in female runners. Fifteen healthy female runners were recruited to run through a 145-m runway with planted force plates at one peculiar speed (3.6 m/s ± 5%) with two kinds of shoe conditions (innovative running shoes vs. normal running shoes) while getting biomechanical data. The perception of shoe characteristics was assessed simultaneously through a 15-cm visual analog scale. The statistical parametric mapping technique calculated the time-series parameters. Regarding 0D parameters, the ankle dorsiflexion angle of innovative running shoes at touchdown was higher, and the peak dorsiflexion angle, range of motion, peak dorsiflexion velocity, and plantarflexion moment on the metatarsophalangeal joint of innovative running shoes during running were significantly smaller than those of normal running shoes (all p < 0.001). In addition, the braking phase and the time of peak vertical force 1 of innovative running shoes were found to be longer than those of normal running shoes (both p < 0.05). Meanwhile, the average vertical loading rate 1, peak vertical loading rate 1, peak braking force, and peak vertical force 1 in the innovative running shoes were lower than those of the normal running shoes during running (both p < 0.01). The statistical parametric mapping analysis exhibited a higher ankle dorsiflexion angle (0–4%, p < 0.05), a smaller knee internal rotation angle (0–6%, p < 0.05) (63–72%, p < 0.05), a decreased vertical ground reaction force (11–17%, p = 0.009), and braking anteroposterior ground reaction force (22–27%, p = 0.043) for innovative running shoes than normal running shoes. Runners were able to perceive the cushioning of innovative running shoes was better than that of normal running shoes. These findings suggested combining the high offset and structure of the midsole would benefit the industrial utilization of shoe producers in light of reducing the risk of running injuries for female runners.